Molecular Characteristics of m6A Regulators and Tumor Microenvironment Infiltration in Soft Tissue Sarcoma: A Gene-Based Study - Kang-Wen Xiao (Frontiers in Bioengineering and Biotechnology, 2022)
Background: N6-methyladenosine (m6A) methylation played a key role in tumor growth. However, the relationship between m6A and soft tissue sarcoma (STS) was still unclear.Methods: The characterization and patterns of m6A modification in STS (TCGA-SARC and GSE17674) were analyzed comprehensively through bioinformatics and real-time polymerase chain reaction (RT-PCR). The effects of different m6A modification patterns on prognosis and immune infiltration of STS were further explored. Differentially expressed gene (DEG) analysis was performed. Moreover, an m6Ascore was constructed by principal component analysis (PCA). In addition, two immunotherapy datasets (IMvigor210 and GSE78220) and a sarcoma dataset (GSE17618) were used to evaluate the m6Ascore.Results: Huge differences were found in somatic mutation, CNV, and expression of 25 m6A regulators in STS. Two modification patterns (A and B) in STS were further identified and the m6A cluster A showed a better clinical outcome with a lower immune/stromal score compared with the m6A cluster B (p < 0.050).In addition to , most STS samples from m6A cluster A showed a high m6Ascore, which was related to mismatch repair and a better prognosis of STS (p < 0.001). In contrast, the m6A cluster B, characterized by a low m6Ascore, was related to the MYC signaling pathway, which led to a poor prognosis of STS. A high m6Ascore also contributed to a better outcome of PD-1/PD-L1 blockade immunotherapy.Conclusion: The modification patterns of 25 m6A regulators in the STS microenvironment were explored comprehensively. The novel m6Ascore effectively predicted the characteristics of the tumor microenvironment (TME) and outcome in STS and provided novel insights for future immunotherapy.